Production of conjugated dienoic and trienoic fatty acids by lactic acid bacteria and bifidobacteria - Terán, Victoria (2015)
The production of conjugated linoleic (CLA) and linolenic (CLNA) acids by lactic acid bacteria (LAB) and bifidobacteria strains was assessed. The initial selection was based on optical density measurements by the UV method and GC analysis. The LAB strains showed a lower ability to synthesise CLA and CLNA. Yet, two Lactobacillus sakei strains were the best producers. Moreover, the production of CLA and CLNA by Lactobacillus mucosae is reported here for the first time. In contrast, bifidobacteria strains were more efficient to synthesise CLA and CLNA. Among these, the t9, t11-CLA was the main isomer, which is a potent anticarcinogenic compound. All tested strains produced the c9,t11,c15-CLNA isomer. High substrate concentrations of LA and LNA negatively affected the conversion rate of CLA and CLNA by Bifidobacterium animalis subsp. lactis INL2, even though the bacterial growth was not affected.